RF and microwave modeling and measurement techniques for compound field effect transistors - Gao, Jianjun, 1968- (SciTech Pub., 2010)
"This book is an introduction to microwave and RF signal modeling and measurement techniques for field effect transistors. It assumes only a basic course in electronic circuits and prerequisite knowledge for readers to apply the techniques and improve the performance of integrated circuits, reduce design cycles and increase their chance at first time success. The first chapters offer a general overview and discussion of microwave signal and noise matrices, and microwave measurement techniques. The following chapters address modeling techniques for field effect transistors and cover models such as: small signal, large signal, noise, and the artificial neural network based."--Pub. desc.
Keywords: Field-effect transistors -- Testing.; Compound semiconductors -- Testing.; Field-effect transistors -- Mathematical models.; Compound semiconductors -- Mathematical models.; Microwave measurements.; Radio measurements.; elektronické knihy; electronic books